Conversations with biographical novelists : truthful fictions across the Globe - Lackey, Michael (Bloomsbury Academic, 2019)
"Interviews with some of the world's most famous biographical novelists that provide new insights into how novelists from China to Morroco to Canada to South Africa deal with the moving boundaries that separate truth, history, and fiction"--